ANALYSIS OF SI PITUNG'S ETHNOMATHEMATICS-BASED HOME STUDY OF GEOMETRY CONCEPTS IN ELEMENTARY SCHOOLS - Alinda Listiyani; Dian Anggraeni Maharbid (Journal Civics And Social Studies, 2023)
Geometry is a branch of mathematics that is often encountered in everyday life and the material taught is quite difficult compared to other material. Based on Jean Piaget's theory of cognitive development, children who are at the elementary school level are in the concrete operational stage. At this stage, the way elementary school students think about mathematics is still firmly rooted in real situations. Ethnomathematics is learning in mathematics by using concepts related to local culture. In addition, incorporating ethnomathematics into learning mathematics can be used as an introduction to culture through the environment around students. The purpose of this study is to analyze more deeply the structure of the Si Pitung House more using the concept of geometric shapes through a cultural or ethnomathematics context. This study uses a type of qualitative research with a cultural descriptive ethnographic approach, with interview, observation, and documentation methods. The purpose of the data collection technique used in this study is to gain an understanding of the geometric concept of geometric shapes in the structure of the Si Pitung House. Meanwhile, of the purpose of the interview technique used in this study was to collect more data and information about the geometric concepts contained in the structure of the Si Pitung House. The results of this study found that there are geometric concepts, such as cubes, beams, pyramids, prisms, tubes, and spheres in the structure of the Si Pitung House.